2016
DOI: 10.1186/s12864-016-2739-6
|View full text |Cite
|
Sign up to set email alerts
|

A de novo transcriptome analysis shows that modulation of the JAK-STAT signaling pathway by salmonid alphavirus subtype 3 favors virus replication in macrophage/dendritic-like TO-cells

Abstract: BackgroundThe Janus kinase (Jak) and signaling transducer activator of transcription (Stat) pathway mediates the signaling of genes required for cellular development and homeostasis. To elucidate the effect of type I IFN on the Jak/stat pathway in salmonid alphavirus subtype 3 (SAV3) infected macrophage/dendritic like TO-cells derived from Atlantic salmon (Salmo salar L) headkidney leukocytes, we used a differential transcriptome analysis by RNA-seq and the Kyoto encyclopedia of genes and genomes (KEGGs) pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…The negligible IFNa response in the BI group has been observed previously in cohabitation infections with SAV [14]. In a recent study, recombinant IFNa applied simultaneously with SAV3 to a TO cell culture was able to induce the rapid transcription of ISGs resulting in a 20-fold reduction of SAV3 RNA compared to cells not treated with IFNa [36]. Clearly the more rapid the induction of IFNa the better protection the host has against SAV.…”
Section: The Anti-viral Responsementioning
confidence: 72%
“…The negligible IFNa response in the BI group has been observed previously in cohabitation infections with SAV [14]. In a recent study, recombinant IFNa applied simultaneously with SAV3 to a TO cell culture was able to induce the rapid transcription of ISGs resulting in a 20-fold reduction of SAV3 RNA compared to cells not treated with IFNa [36]. Clearly the more rapid the induction of IFNa the better protection the host has against SAV.…”
Section: The Anti-viral Responsementioning
confidence: 72%
“…The high transcript abundance of SOCS1 has been suggested to be a consequence of SAV infection and may be a survival strategy for the virus. Increasing SOCS1 mRNA expression may subsequently inhibit signal transduction via the JAK/STAT pathway and may contribute to viral replication [31,32]. In our previous study, we observed a reduction in ISG and Mx expression in the IM-B group [19] that partially may be due to up-regulation of the SOCS1 after SAV infection.…”
Section: Rig-1 Showed Similar Patterns Of Transcription As Another Prrmentioning
confidence: 86%
“…This is mainly because there has been a general lack of appropriate tools able to identify and characterize viruses collected from environmental samples. However, the emergence of high throughput next generation sequencing (NSG) in recent years has not only enhanced our understanding of host responses to viral infections (Chu et al, 2015; Dahle et al, 2015; Xu et al, 2015, 2016a,b; Liu et al, 2016), but it has opened a great avenue for identification of viruses found in different aquatic environments using metagenomics analyses (Suttle, 2005, 2007; Djikeng et al, 2009; Kim et al, 2015). Viral metagenomics is a culture independent sequencing tool able to identify a large number of viral genomes from the same sample at the same time without prior knowledge of genomic sequences of the viruses to be identified (Handelsman, 2004; Bibby, 2013).…”
Section: Introductionmentioning
confidence: 99%